Pleasures of skill and moral conduct - Armin Falk; Nora Szech (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
As was recognized by Bentham, skillfulness is an important source of pleasure. Humans like achievement and to excel in tasks relevant to them. This paper provides controlled experimental evidence that striving for pleasures of skill can have negative moral consequences and causally reduce moral values. In the study, subjects perform an IQ-test. They know that each correctly solved question not only increases test performance but also the likelihood of moral transgression. In terms of self-image, this creates a trade-off between signaling excellence and immoral disposition. We contrast performance in the IQ-test to test scores in an otherwise identical test, which is, however, framed as a simple questionnaire with arguably lower self-relevance. We find that subjects perform significantly better in the IQ-test condition, and thus become more willing to support morally problematic consequences. Willingness to reduce test performance in order to behave more morally is significantly less pronounced in the IQ versus the more neutral context. The findings provide controlled and causal evidence that the desire to succeed in a challenging, self-relevant task has the potential to seduce subjects into immoral behaviors and to significantly decrease values attached to moral outcomes.
Keywords: 330